2002
DOI: 10.1097/00004872-200203000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin improves endothelial function in spontaneously hypertensive rats through a superoxide dismutase mediated antioxidant effect

Abstract: Simvastatin promotes intracellular antioxidant systems, fundamentally SOD, restoring endothelial function but not having any effect on blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 31 publications
5
48
0
1
Order By: Relevance
“…26 Recent in vivo 27,28 and in vitro 29,30 studies have shown that fluvastatin has more potent antioxidative effects than other statins, including pravastatin, simvastatin, cerivastatin, and atorvastatin, although simvastatin also has some antioxidant effect. 31 Thus, the powerful antioxidant properties of fluvastatin may have contributed to the reduction in PWV.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recent in vivo 27,28 and in vitro 29,30 studies have shown that fluvastatin has more potent antioxidative effects than other statins, including pravastatin, simvastatin, cerivastatin, and atorvastatin, although simvastatin also has some antioxidant effect. 31 Thus, the powerful antioxidant properties of fluvastatin may have contributed to the reduction in PWV.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the ability of aspirin not to interfere with the synthesis of PGI 2 and its ability to enhance NO production and/or its half-life by decreasing oxidative stress could be responsible for its beneficial actions. These results (Carneado et al, 2002;El Midaoui et al, 2002) suggest that the balance between O 2 ÀK , NO, and PGI 2 is critical in the prevention of hypertension.…”
Section: Introductionmentioning
confidence: 87%
“…The role of O 2 ÀK in hypertension is not without controversy. For instance, simvastatin, a hydroxymethylglutaryl coenzyme A reductase inhibitor, used in the management of hyperlipidemias is known to behave like an anti-oxidant: simvastatin increases the activities of SOD and glutathione peroxidase and thus improves endothelial function (Carneado et al, 2002). No reduction in the increased blood pressure was noted in simvastatin-treated SHR, and subjects with hypertension, suggesting that O 2 ÀK may not always be responsible for hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins have antiinflammatory and anti-oxidant properties by their inhibition of neutrophil activity, reduction of oxidative stress, and maintenance of vascular integrity. [26][27][28] However, it still remains to be determined whether statin therapy, as well as ARB use, is correlated with peptic ulcer or NSAID-induced mucosal injuries in humans. …”
Section: Risk Factors For Upper Gi Bleedingmentioning
confidence: 99%